Diálogo social y negociación colectiva a escala sectorial en la Unión Europea. Limitaciones y perspectivas - Köhler, Holm-detlev; González Begega, Sergio (Cuadernos de Relaciones Laborales, 2008)
The lack of stable and clear structures for dialogue and negotiation at sectoral level represents a fundamental problem threatening future developments in European industrial relations. In fact, whereas interprofessional and firm level European industrial relations underwent an important improvement after the Social Protocol of Maastricht, advances in sectoral level have been much more limited. This article attempts to analyze the two different but not mutually exclusive ways to develop this level of dialogue and negotiation: the European Sectoral Social Dialogue and the various trade union initiatives for transnational coordination of collective bargaining. We will present the current situation of the debate on these topics and we will connect our arguments with the consequences the latests economic and political projects of the European Union (Economic and Monetary Union and enlargement) are having on European industrial relations.